Документи архівно-слідчих справ як джерело вивчення методів провадження слідства органами НКВС на Одещині в період «великого терору» 1937–1938 рр. - Петровський, Е. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2007)
Based on source study analysis of criminal cases, the author characterized the investigatory methods used by administrative department of the NKVD in Odesa region during «the great terror» of 1937–1938.